Jurassic world : junior novelization - Lewman, David (Random House Children's Books, 2015)
Jurassic World is the long-awaited next installment of the groundbreaking Jurassic Park series. T. Rex's, Velociraptors, Triceratops--as well as some all-new dinosaurs--will roar across the screen in this epic action-adventure directed by Colin Trevorrow starring Chris Pratt, Bryce Dallas Howard, Ty Simpkins and Nick Robinson! Jurassic World The Special Edition Movie Novelization retells the whole exciting adventure and features sixteen pages of full-color scenes from the movie.